Problems of Reading the Quran in Eight Semester Students of Islamic Religious Education Department (IAIN) Ternate - Hendra Mubin; Jasin Ibrahim; Adiyana Adam; Nurbaini Nasir (PT Mattawang Mediatama Solution, 2023)
Al-Quran is the first source of Islamic law. Ternate State Islamic Institute is an Islamic Institute. And students who have graduated from the green campus will certainly do their service to the community for the knowledge they gain. Islamic religious education major, one of the skills that must be smart in reading the Koran. This is what we then want to ascertain whether there are still students whose majors (PAI) cannot read the Qur'an? This study uses a type of qualitative research. The method we use is the interview method using the Google Form. The results we got were that only a small proportion of IAIN Ternate students could not read the Qur'an properly. Even if only a small part, but this is a problem that must be considered. We suggest that a green campus must be able to present a Al-Qur'an reading program so that students can learn to read the Al-Qur'an well.